2020
DOI: 10.1016/j.acra.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Well-Being and Education in Radiology Residencies: A Survey of the Association of Program Directors in Radiology

Abstract: Rationale and Objectives: The COVID-19 pandemic has forced rapid evolution of the healthcare environment. Efforts to mitigate the spread of the virus through social distancing and shelter-at-home edicts have unintended consequences upon clinical and educational missions and mental well-being of radiology departments. We sought to understand the impact of the COVID-19 pandemic on radiology residencies with respect to the educational mission and perceptions of impact on well-being.Materials and Methods: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 33 publications
4
74
1
Order By: Relevance
“…This result is in line with a recent survey of members of the Association of Program Directors in Radiology which found that 70% of respondents (75/107) felt that the educational mission in their radiology department was at least moderately negatively impacted by COVID-19 related changes. 42 Importantly, 31% of survey respondents (22/72) in our study indicated concern that COVID-19 related changes in resident education would impact the likelihood of current radiology trainees pursuing a career in pediatric radiology in their countries.…”
Section: N P R E S Smentioning
confidence: 74%
“…This result is in line with a recent survey of members of the Association of Program Directors in Radiology which found that 70% of respondents (75/107) felt that the educational mission in their radiology department was at least moderately negatively impacted by COVID-19 related changes. 42 Importantly, 31% of survey respondents (22/72) in our study indicated concern that COVID-19 related changes in resident education would impact the likelihood of current radiology trainees pursuing a career in pediatric radiology in their countries.…”
Section: N P R E S Smentioning
confidence: 74%
“…In Stage 4, ACGME common program requirements for well-being are paramount, going beyond ensuring adequate resident personal protective equipment to assuring mental health services are readily available to all residents and faculty. In a recent survey, Program Directors perceived significant negative impact of the pandemic on resident morale, and reported actual negative impact on their own morale [3]. Further negative impacts noted by the authors include additional challenges from limited or deferred vacation requests that ensued because of redeployment in Stage 3, as well as the need to offer compensatory increased case volumes to assure residents meet ACGME graduation requirements.…”
Section: Stage 4 Increased Non-covid Clinical Demandsmentioning
confidence: 99%
“…While clinical, educational, and well-being impacts in Stage 1-3 have been well-documented [3] T may be spread over multiple sites. Conceived as a solution to canceled appointments and delayed medical needs during the COVID-19 peak, work assignment changes to meet the post-peak rebound demand may include longer hours, off-setting work shifts, and expanded responsibilities.…”
Section: Stage 4 Increased Non-covid Clinical Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 A study on radiology resident well-being during the pandemic reported decreased morale, especially in programs with redeployment. 47 For residents already anxious about their own education, additional teaching responsibilities may contribute to burnout. In addition, both undergraduate and postgraduate learners may feel isolated during this time of predominantly virtual learning.…”
Section: Structured Teachingmentioning
confidence: 99%